The skill of nursing students trained in the evaluation of electrocardiographic trace: a comparison with emergency nurses - Rubbi, Ivan; Carvello, Maicol; Bassi, Veronica; Triglia, Carmela; Di Lorenzo, Rosaria; Cremonini, Valeria; Artioli, Giovanna; Ferri, Paola (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: Cardiovascular diseases represent the main cause of death in Italy. Early recognition of pathological electrocardiographic (ECG) trace is an important skill for nurses. The theoretical knowledge and the practical skills on the recognition of pathological ECG trace of trained nursing students were compared with those of emergency nurses.Methods: The study involved 35 nursing students and 41 nurses from the emergency room, emergency medicine and ambulance service. Students were previously trained through a theoretical and practical ECG course. The data were collected using  two questionnaires aimed at evaluating in the two groups the ability to recognize electrocardiographic signs. The tools were uploaded to an online platform and remotely administered.Results: Both the students and the nurses showed a satisfactory theoretical knowledge of the ECG trace, with a statistically significant difference in favor of the nurses. Regarding practical skills, both groups showed difficulty in recognizing pathological electrocardiographic signs, particularly blockages and acute coronary syndromes.Conclusions: Nursing students' knowledge of ECG did not differ much from that of nurses. Training through simulation probably played a key role in improving the skill of ECG evaluation among students. More theoretical and practical courses on ECG should be recommended in Nursing Programme.Keywords: nurse, education, simulation, knowledge, ECG interpretation, emergency department